Inhibitory Effect of Methyleugenol on IgE-Mediated Allergic Inflammation in RBL-2H3 Cells - Feng Tang; Feilong Chen; Xiao Ling; Yao Huang; Xiaomei Zheng; Qingfa Tang; Xiaomei Tan (Hindawi Limited, 2015)
Allergic diseases, such as asthma and allergic rhinitis, are common. Therefore, the discovery of therapeutic drugs for these conditions is essential. Methyleugenol (ME) is a natural compound with antiallergic, antianaphylactic, antinociceptive, and anti-inflammatory effects. This study examined the antiallergic effect of ME on IgE-mediated inflammatory responses and its antiallergy mechanism in the mast cell line, RBL-2H3. We found that ME significantly inhibited the release of β-hexosaminidase, tumor necrosis factor- (TNF-) α, and interleukin- (IL-) 4, and was not cytotoxic at the tested concentrations (0-100 μM). Additionally, ME markedly reduced the production of the proinflammatory lipid mediators prostaglandin E2 (PGE2), prostaglandin D2 (PGD2), leukotriene B4 (LTB4), and leukotriene C4 (LTC4). We further evaluated the effect of ME on the early stages of the FcεRI cascade. ME significantly inhibited Syk phosphorylation and expression but had no effect on Lyn. Furthermore, it suppressed ERK1/2, p38, and JNK phosphorylation, which is implicated in proinflammatory cytokine expression. ME also decreased cytosolic phospholipase A2 (cPLA2) and 5-lipoxygenase (5-LO) phosphorylation and cyclooxygenase-2 (COX-2) expression. These results suggest that ME inhibits allergic response by suppressing the activation of Syk, ERK1/2, p38, JNK, cPLA2, and 5-LO. Furthermore, the strong inhibition of COX-2 expression may also contribute to the antiallergic action of ME. Our study provides further information about the biological functions of ME.